Spatial Prediction of Landslide Susceptibility Using the Information Value Model: A Case Study of Purworejo Regency, Central Java, Indonesia - Fathin Aulia Rahman; Syifa Hanifa (Jagratara: Journal of Disaster Research, 2025)
Purworejo Regency is an area that has a high level of landslide proneness. So it is necessary to conduct a landslide susceptibility analysis study. This study aims to study landslides using landslide modeling analysis. Data processing based on geographic information system with ArcGIS application. The parameter maps used are; slope, direction to the slope, elevation, rainfall, NDVI, distance from the river (buffer), distance from the highway (buffer), and distance from fault (buffer). The analysis technique uses statistical analysis with the Information Value Model method. The results showed: 1) spatial modeling using the IVM method was able to describe the spatial distribution of landslide susceptibility levels in Purworejo Regency. The Northeast to the upper North regions has a high vulnerability to landslides. More detailed knowledge is needed to be able to apply landslide disaster mitigation strategies so that mitigation can run effectively. 2) the results of data processing obtained by the total IVM are classified into 5 classes for landslide vulnerability in Purworejo Regency, including the following: Very Low (0.0275- 0.0365) Low (0.0366 - 0.0401) Medium (0.0402 - 0.0455) High (0.04556 - 0.2528 ) Very High (0.2529 - 0.2582).